(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Special Economic Zones (SEZs) have become a key institutional instrument for enhancing national investment attractiveness, particularly in developing and transition economies. This study examines the institutional effectiveness of SEZs in improving the investment climate by analyzing their regulatory frameworks, governance mechanisms, and incentive structures. The research focuses on how institutional quality within SEZs—such as transparency, administrative efficiency, legal guarantees, and infrastructure provision—influences foreign direct investment inflows and overall investment performance.